PENERAPAN ALGORITMA KRIPTOGRAFI AES (ADVANCED ENCRYPTION STANDARD) DAN ALGORITMA KOMPRESI RLE (RUN LENGTH ENCODING) UNTUK PENGAMANAN FILE DOKUMEN - Rifky Priambudi (2021)
Document files are sensitive data where there is often theft and misuse to change the contents of the file. In storage by an individual or a particular organization, the file is stored in a computer or database system. The rise of data theft in the form of important document files that occur in large companies or individuals is certainly a clear violation of applicable laws. So that these irresponsible parties benefit from data theft. This study aims to develop or secure digital images, namely document files with more efficient results by using a combination of the AES algorithm in the encryption process and the RLE algorithm in the compression process. The AES algorithm is used as the encryption and decryption process for the file, while the RLE algorithm is used as the compression and decompression process. From the results of this study, the combination of the AES algorithm and the RLE algorithm succeeded in securing document files in a more efficient way and results. Where in the process of compressing and decompressing document files that have quite a lot of characters in them can be completed quickly in the encryption and compression process and vice versa when decompressing and decrypting the resulting file is also relatively the same and stable as the original file before being processed.